2023
DOI: 10.1186/s12995-023-00371-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential Risk of SARS-CoV-2 Infection by Occupation: Evidence from the Virus Watch prospective cohort study in England and Wales

Abstract: Background Workers across different occupations vary in their risk of SARS-CoV-2 infection, but the direct contribution of occupation to this relationship is unclear. This study aimed to investigate how infection risk differed across occupational groups in England and Wales up to April 2022, after adjustment for potential confounding and stratification by pandemic phase. Methods Data from 15,190 employed/self-employed participants in the Virus Wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…In this study, the median age of the study population was 30.0 years (interquartile range [IQR]: 14-41.2). Notably, the unvaccinated cohort were mainly under 18 years old, while the vaccinated groups were over 19 years old, which resulted in a significantly higher median age compared to the unvaccinated cohort (36 [IQR: [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]] and 36.5 [IQR: 30-47.4] vs. 13.0 [IQR: 9-26], p<0.001). The results were similar to other reported studies which showed that most COVID-19 infections occurred in the 19-30-year age groups [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the median age of the study population was 30.0 years (interquartile range [IQR]: 14-41.2). Notably, the unvaccinated cohort were mainly under 18 years old, while the vaccinated groups were over 19 years old, which resulted in a significantly higher median age compared to the unvaccinated cohort (36 [IQR: [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]] and 36.5 [IQR: 30-47.4] vs. 13.0 [IQR: 9-26], p<0.001). The results were similar to other reported studies which showed that most COVID-19 infections occurred in the 19-30-year age groups [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that healthcare staff had higher potential for getting the disease than the others because of exposure to infection in the hospital environment 28 , 29 . Further investigations should be conducted to explore the specific factors contributing to the increased risk among these occupational groups 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 infections and mortality reportedly varied over time and by occupation during the pandemic [ 4 , 5 , 6 , 12 , 13 , 14 , 15 , 16 , 17 ], being influenced by a number of factors, including vaccine uptake, indoor versus outdoor work environment, poor ventilation, exposure to contaminated surfaces, number of people in the worksite, social distancing, efficiency of contract tracing and observation of non-pharmaceutical risk reduction measures [ 5 , 6 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Occupation was classified into the following categories triangulating occupation, exposure risk, and employment status: higher exposure risk occupation, lower exposure risk occupation, retired, not in employment, and unknown/other status. Further details of occupational categories are provided in the , and details of the occupational coding process are provided in related Virus Watch analyses [ 35 ].…”
Section: Methodsmentioning
confidence: 99%